 # EXAMPLE 3 Combining Like Terms a. 3x + 4x = (3 + 4)x = 7x b.

## Presentation on theme: "EXAMPLE 3 Combining Like Terms a. 3x + 4x = (3 + 4)x = 7x b."— Presentation transcript:

EXAMPLE 3 Combining Like Terms a. 3x + 4x = (3 + 4)x = 7x b.
Distributive property = 7x Add inside grouping symbols. b. –9y + 7y + 5z = (–9 + 7)y + 5z Distributive property = –2y + 5z Add inside grouping symbols.

Simplifying an Expression
EXAMPLE 4 Simplifying an Expression a. 2(4 + x) + x = 8 + 2x + x Distributive property = 8 + 3x Combine like terms. b. –5(3x – 6) + 7x = –15x x Distributive property = –8x + 30 Combine like terms.

Simplify the expression by combining like terms.
GUIDED PRACTICE for Examples 3 and 4 Simplify the expression by combining like terms. 7. 2(x + 4) + 3x – 5 2(x + 4) + 3x – 5 = 2x x – 5 Distributive property = 5x + 8 + (–5) Add. = 5x + 3 Combine like terms.

Simplify the expression by combining like terms.
GUIDED PRACTICE for Examples 3 and 4 Simplify the expression by combining like terms. 8. 5y + 9z – 7 – 3y 5y + 9z – 7 – 3y = (5 – 3)y + 9z – 7 Distributive property = 2y + 9z – 7 Combine like terms.

Simplify the expression by combining like terms.
GUIDED PRACTICE for Examples 3 and 4 Simplify the expression by combining like terms. 9. –3(6x + 2y) + 22x –3(6x + 2y) + 22x = –18x – 6y + 22x Distributive property = 4x – 6y Combine like terms.

Download ppt "EXAMPLE 3 Combining Like Terms a. 3x + 4x = (3 + 4)x = 7x b."

Similar presentations